A case report of rare variant: the uncommon encounter “sellar spine” - K. R. Arvind; Joy Varghese; Darshil Jadhav (Egyptian Journal of Neurosurgery)
Abstract Background Sellar spine is a rare entity that presents as a bony projection from the dorsum sella and protrudes into the pituitary fossa. As they can mimic a pituitary adenoma, it is important to consider this entity in the differential diagnosis of a sellar lesion to avoid a delay in diagnosis or surgery. Case Report A 29-year-old male presented with a history of headaches relieved with over-the-counter medications for the past 2 years. He was initially evaluated with an MRI brain at his hometown and referred to us as a pituitary tumour. Physical and neurological examination were unremarkable. Ophthalmological examination and hormonal evaluation were also done and normal. A repeat imaging done at our institute with an MRI brain with pituitary protocol revealed a non-enhancing lesion on contrast and arising from dorsum sella with the same intensity as that of bone on T1- and T2-weighted images with no mass effect seen. A CT brain screening revealed a bony spur, consisting of a narrow stalk with a mildly distended tip, arising from the dorsum sella in the midline, projecting anterosuperiorly into the pituitary fossa. So, a diagnosis of the sellar spine was made and a non-urgent neurosurgical review with repeat imaging and hormonal profile was advised on follow-up. Conclusion Sellar spine can be either asymptomatic or cause neuroendocrine manifestations in a few patients. MRI can have variable signal intensity depending upon the marrow content and thus can mimic a pituitary adenoma and so CT is the imaging of choice. Although being a rare anomaly, both neurosurgeons and radiologists must be aware of this finding on imaging to avoid unnecessary invasive surgery and delay in diagnosis.